Optimizing Chronic Disease Management: The Comprehensive Role and Impact of Exercise Interventions in Public Health - Zhao Xingyu (Ilmu Inovasi Nusantara, 2024)
With the development of the social economy, changes in living habits, and population aging, the incidence of chronic diseases has increased significantly, becoming a major challenge for global public health. This study explores the significant role and effects of exercise intervention in the management of chronic diseases. Chronic diseases have high mortality rates, substantial disease burdens, and significant impacts on medical expenses. Traditional prevention and control strategies centered on treatment show limitations in addressing these issues. This study aims to examine the effects of exercise intervention as a non-pharmacological therapy, which offers low-cost and high-benefit advantages in the prevention and treatment of chronic diseases. Through systematic review and empirical analysis, this research elaborates on the effects of exercise intervention in improving function and reducing pain in arthritis patients, preventing falls in the elderly, enhancing respiratory function in COPD patients, controlling blood glucose in type 2 diabetes patients, and reducing obesity symptoms. The study's findings indicate that exercise intervention has a significant positive impact on various aspects of chronic disease management. These interventions not only improve the physical condition of patients but also reduce the overall disease burden and medical costs. This research emphasizes the importance of personalized and scientific formulation and implementation of exercise interventions. Specific recommendations regarding exercise intervention are provided for future chronic disease prevention and control strategies. Thus, this study offers precise and applicable guidelines for improving the management and prevention of chronic diseases through exercise intervention